Design of a GMP system for the seafood market in the Pedro Carbo canton. - Fierro Aguilar, Jaime Patricio; Montenegro Morán, Freddy Luis; Gómez Chávez, Gómez Chávez (Ingeniería Química y Desarrollo, 2024)
The present research work carried out in the municipal market of the Pedro Carbo canton in the area of seafood, to each and every one of the merchants settled in the place, has as its main objective the design of a Good Manufacturing Practices (BPM) system whose fundamental purpose is to cover all the shortcomings found in the workplace, thus strongly improving the way in which these are developed in their work area both in the handling, reception, refrigeration, transportation of everything that is sold in the place. For the analysis of the breaches, a diagnosis was made using an Ishikawa diagram in the area of shellfish to know the current status of the same and establish actions at the points required based on the standard. The purpose of the design is to establish a feasible solution to the problem based on the current BPM regulations in the seafood area of the Pedro Carbo canton market.
Keywords: Good Manufacturing Practices; Prevention; Hygiene; Normative; Food; Consumption; Seafood; Shortcomings